2012
DOI: 10.1159/000337000
|View full text |Cite
|
Sign up to set email alerts
|

EEG Vigilance Regulation Patterns and Their Discriminative Power to Separate Patients with Major Depression from Healthy Controls

Abstract: Background/Aim: Recently, a framework has been presented that links vigilance regulation, i.e. tonic brain arousal, with clinical symptoms of affective disorders. Against this background, the aim of this study was to deepen the knowledge of vigilance regulation by (1) identifying different patterns of vigilance regulation at rest in healthy subjects (n = 141) and (2) comparing the frequency distribution of these patterns between unmedicated patients with major depression (MD; n = 30) and healthy controls (HCs;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 57 publications
4
54
0
Order By: Relevance
“…Our finding of more stable EEG vigilance regulation in MDD is in agreement with previous studies [2,3] and extends past findings using a refined version of the VIGALL algorithm in a larger sample of unmedicated depressed patients. The pattern across the 15-min EEG sampling frame of fewer declines into lower EEG vigilance stages, and a greater percentage of high EEG vigilance stages in the unmedicated depressed group, supports the theory of hyperstable arousal regulation in MDD [1].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of more stable EEG vigilance regulation in MDD is in agreement with previous studies [2,3] and extends past findings using a refined version of the VIGALL algorithm in a larger sample of unmedicated depressed patients. The pattern across the 15-min EEG sampling frame of fewer declines into lower EEG vigilance stages, and a greater percentage of high EEG vigilance stages in the unmedicated depressed group, supports the theory of hyperstable arousal regulation in MDD [1].…”
Section: Discussionsupporting
confidence: 93%
“…Percentages of EEG vigilance stages were computed by dividing the number of segments of a given stage by the number of nonartifact segments [for a detailed description, see [3]]. Furthermore, according to the respective vigilance stage, each segment was allocated to a measure ranging from the value 7 (highest vigilance stage W) to 1 (sleep onset stage C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hegerl et al [38] and Olbrich et al [39] reported that MDD is associated with an increased EEG vigilance during rest with fewer and slower declines to lower vigilance stages during a 15-min resting condition. The appeal of this marker reflecting a high tone of CNS arousal can be found in the linkage between clinical symptoms and EEG parameters of wakefulness regulation.…”
Section: Biomarkersmentioning
confidence: 99%
“…Regarding VIGALL's application in clinical groups and for treatment response prediction, several studies have been published recently: in major depression earlier EEG studies [58,59] as well as more recent VIGALLbased studies [60,61] revealed that depressed patients are characterized by a hyperstable arousal regulation, i.e. they show delayed or no decline to lower EEG vigilance stages under resting conditions.…”
Section: Application Of Vigallmentioning
confidence: 99%